Protective Effect of Black Brick Tea Infusion against Ethanol-Induced Acute and Chronic Gastrointestinal Dysfunction in Mice - SHEN Lan, WU Shenqun, ZHANG Xiaoyu, LI Yao, QIN Lilan, FENG Xiaoguang, YANG Xiaoping (Shipin Kexue, 2025)
Gastrointestinal dysfunction can lead to a variety of gastrointestinal diseases, significantly affecting health. In this study, we aimed to explore the protective effect of black brick tea (BBT) infusion against acute and chronic gastrointestinal dysfunction in mice, which were induced by intragastric administration of 40% and 75% ethanol solutions, respectively. The results showed that compared with the model group, BBT infusion was effective in maintaining the morphology of the gastrointestinal mucosa, mitigating gastric mucosal damage, increasing the serum activity of superoxide dismutase, and reducing the concentrations of malondialdehyde, tumor necrosis factor α, and interlrukin 6. Additionally, BBT infusion effectively increased the gastric emptying rate and small intestinal propulsion rate in chronic alcohol-exposed mice, as well as the serum contents of motilin and gastrin, while reducing the contents of vasoactive intestinal peptide and somatostatin. In conclusion, BBT infusion exhibited a protective effect on acute and chronic gastrointestinal dysfunction in mice, presumably regulating gastrointestinal hormone secretion, improving oxidative stress response and reducing inflammatory factor levels in serum.